Chloe, the topaz fairy - Meadows, Daisy (Meadows, Daisy. Jewel fairies, 2007)
Rachel and Kirsty must retrieve the magic topaz which Jack Frost has stolen so that Chloe, the topaz fairy can change girls into fairies and goblins into teddy bears.